Photocatalytic degradation of C.I. reactive blue 19 by using novel nano BiVO4-coated cotton fabric. (May 2015) - Wang, Zhenhua; Xuan, Jian; Liu, Baojiang; He, Jinxin
Bismuth vanadate-coated cotton fabric was synthesized by a chemical bath deposition method at low temperature (≤100℃) and characterized by using scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction and UV-V is diffuse reflectance spectroscopy. Its photocatalytic activities were evaluated by decomposition of C.I. reactive blue 19 in aqueous solution under visible light irradiation. The as-prepared composite possesses excellent photocatalytic activity for the degradation of liquid contamination especially in static system due to its large specific surface area. The reduction of total organic carbon (about 48.0% after 4 h of irradiation) showed that the mineralization of C.I. Reactive Blue 19 over the bismuth vanadate-coated cotton fabric is realizable. Moreover, the preparation of the composites is convenient for potential practical application. The formation mechanism of bismuth vanadate on the fabric was also discussed preliminarily.